PENGETAHUAN DAN PENERIMAAN TERAPI KOMPLEMENTER PADA IBU NIFAS BERBASIS KEARIFAN LOKAL - Rahayu Widaryanti (Medika Respati : Jurnal Ilmiah Kesehatan, 2020)
Background: Indonesia is a country that has socio-cultural diversity and has a tradition to maintain health, especially for postpartum mothers. Management of services for postpartum mothers in addition to evidence-based midwifery, sometimes postpartum mothers also use complementary therapy to overcome complaints experienced by mothers. As the use of herbal ingredients to increase milk production or to reduce pain in perinuim wounds, in addition there are also several methods to accelerate the recovery of postpartum maternal health conditions using pilis, parem, tapel or the use of a curve. Objective: This study aims to determine the level of knowledge and acceptance of complementary therapy in postpartum mothers based on local wisdom. Method: This type of research is quantitative with a retrospective approach, sampling technique with purposive sampling. Data collection is done by questionnaire. Result: The majority of postpartum mothers' knowledge about complementary therapy was low at 52.8%. complementary therapies that often exist in the community, namely the use of pilis, tapel, parem, herbal medicine and curved or octopus. The highest acceptance of complementary therapy was 71.7% of the herbal medicine and the lowest was 1.9% in parem. Conclusion: Complementary therapy has many benefits but has not been used maximally in the community because not many people know about the efficacy of these therapies, besides that complementary therapy in the community is not yet available in a modern and practical form so that not many people use it.